First detection and analysis of a fish circovirus - Lőrincz, Márta; Cságola, Attila; Farkas, Szilvia L; Székely, Csaba; Tuboly, Tamás (Journal of general virology, 2011)
Circoviruses are present worldwide in birds and pigs but their occurrence in fish has not yet been reported. Recently, increased mortality was observed in barbel fry (Barbus barbus) in Hungary. This paper reports the detection of previously unknown circular viral DNA genomes in barbels by the use of a circovirus-specific wide-range nested PCR. The analysis of two complete genomes (Barbel circovirus, BaCV1 and BaCV2) indicated that they belonged into a new genetic group within the family Circoviridae, distinct from known circoviruses and circovirus-like genomes. Their genome size was 1957 bases and contained two major ORFs similar to the capsid and replication-associated protein genes of circoviruses. A connection between the presence of the virus and clinical manifestations of the infection could not be proved.